Laro sa baga - Roño, Chito S.; Aquino, Angel; Morales, Carlos; Mina, Ara.; Wilson, Monique; Gil, Mark.; Picache, Cherry Pie 1970-.; Escaño, Cholo; Reyes, Edgar; Barry, Malu.; Regal Entertainment, Inc. ([Philippines] Regal Entertainment, Inc., 2000)
The movie is about Ding's inclination to answer all his sexual urges but eventually learns that nothing in the world of carnal desires is worth anything without the power of love. He develops an infatuation to his godmother/surrogate parent Carmen. Realizing that his infatuation is useless, he falls for Dee, Carmen's adopted daughter.
Based on the novel by Edgardo Reyes.
In Filipino with English subtitles.
Videodisc release of the 1999 film.
Production design, Mike Guizon ; Art directors, Gene de Leon, Pipo Santos, Robert Jose ; SMusical director, Jessie Lasaten ; Director of photography, Niel Daza ; Story and screenplay: Edgardo Reyes ; Film editor, Man
Angel Aquino, Carlos Morales, Ara Mina, Monique Wilson, Mark Gil, Cherry Pie Picache, Cholo Escaño, Malu Barry.
Keywords: Adopted children -- Drama; Man-woman relationships -- Drama